1979
DOI: 10.1007/bf01821121
|View full text |Cite
|
Sign up to set email alerts
|

On the age of the Vedrette di Ries (Rieserferner) massif and its geodynamic significance

Abstract: ZusammenfassungFiir eine radiometrische Gesamtgesteinsanalyse yon etwa vierzig Proben des Rieserferner-Massivs, hat man sich der Rb/Sr Methode bedient.Die Proben wurden in ftinf Gruppen zusammengestellt. Zwischen diesen Oligoz~insehmelzen und der Tauernmetamorphose wird eine genetisehe Bindung vorgeschlagen. AbstractThe Rb/Sr whole rock method was used to carry out radiometric analyses on about forty samples from the Vedrette di Ries massif. The samples were arranged in five sample groups. The age of this mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…The K/Ar-biotite cooling ages obtained excellently fit the age pattern observed in former investigations (Borsi et al 1979;Hammerschmidt 1981;Prochaska 1981). Cooling ages north of the DAV Line increase from around 17 Ma at the Rensen Pluton in the west to 27 Ma at the western end of the Rieserferner Pluton (Fig.…”
Section: New K/ar Mica and Fission-track Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The K/Ar-biotite cooling ages obtained excellently fit the age pattern observed in former investigations (Borsi et al 1979;Hammerschmidt 1981;Prochaska 1981). Cooling ages north of the DAV Line increase from around 17 Ma at the Rensen Pluton in the west to 27 Ma at the western end of the Rieserferner Pluton (Fig.…”
Section: New K/ar Mica and Fission-track Resultssupporting
confidence: 85%
“…This age is interpreted to reflect cooling after Cretaceous metamorphism (Stöckhert 1984). Further to the north, strongly decreasing K/Ar white-mica cooling ages overlap within error limits with Rb/Sr white-mica ages, suggesting rapid Borsi et al (1979) and K/Ar-muscovite ages from earlier investigations (see insert), and new data. Indicated are the two analysed pegmatitic rocks from the basement in the south of the DAV Line yielding an Early Jurassic age.…”
Section: New K/ar Mica and Fission-track Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In the case of the sample from the Steinernes Meer block (Table 1; Fig. 5b), the age of the euhedral crystals (33.11.5 Ma) is identical to the age of the pronounced peak of activity of the main Periadriatic magmatism in Oligocene times (~33±30 Ma; Borsi et al 1979;Blanckenburg and Davies 1995). Frisch et al (1998Frisch et al ( , 1999 and Brügel et al (2000) showed that the Periadriatic intrusive bodies presently exposed on the surface were topped by volcanic edifices in Oligocene times, which are completely eroded today.…”
Section: Zircon Fission-track Datamentioning
confidence: 64%
“…Due to sinistral shearing, contact-related andalusite porphyroblasts are transformed into s-clasts, where syndeformational growth of white mica occurs. White mica±andalusite pairs yielded a Rb±Sr microsampling age of 30.14.6 Ma (Müller et al 2000b), which is similar to the age of intrusion of the Rieserferner pluton (313 Ma; Borsi et al 1978b). Ages of fault rocks collected along various PAF-related faults (North Giudicarie, Tonale, Mauls, DAV) provide direct evidence for Oligocene deformation.…”
Section: Oligocene (32±25 Ma)mentioning
confidence: 71%